2y-4x=8forx

Simple and best practice solution for 2y-4x=8forx equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y-4x=8forx equation:


Simplifying
2y + -4x = 8forx

Reorder the terms:
-4x + 2y = 8forx

Solving
-4x + 2y = 8forx

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8forx' to each side of the equation.
-4x + -8forx + 2y = 8forx + -8forx

Reorder the terms:
-8forx + -4x + 2y = 8forx + -8forx

Combine like terms: 8forx + -8forx = 0
-8forx + -4x + 2y = 0

Add '-2y' to each side of the equation.
-8forx + -4x + 2y + -2y = 0 + -2y

Combine like terms: 2y + -2y = 0
-8forx + -4x + 0 = 0 + -2y
-8forx + -4x = 0 + -2y
Remove the zero:
-8forx + -4x = -2y

Combine like terms: -2y + 2y = 0
-8forx + -4x + 2y = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(-4forx + -2x + y) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-4forx + -2x + y)' equal to zero and attempt to solve: Simplifying -4forx + -2x + y = 0 Solving -4forx + -2x + y = 0 Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. -4forx + -2x + y + -1y = 0 + -1y Combine like terms: y + -1y = 0 -4forx + -2x + 0 = 0 + -1y -4forx + -2x = 0 + -1y Remove the zero: -4forx + -2x = -1y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| -2+8=-7+9 | | 10c^2-8c= | | 4x+20=48 | | 425-c=152 | | -15(z-899)=-930 | | 6a-42=2a-a | | -16+3+m=-7+17 | | -13(j-968)+125=385 | | -z/12=5 | | 4w^2-5=9w | | 4m+5(m+2)=1 | | 8x-(4x+8)=8 | | dx+g=0 | | 3x+-2y=zfory | | 3r=-45 | | -0.6+0.5x+4=5 | | 5(x+2)+4x=55 | | 2m-9m=12 | | 3m^2-18=0 | | 25(b+826)-804=-29 | | P=120-0.03x | | 3r+11s= | | 5N(-8+4T)= | | 3(w-93)+99=24 | | Y=lnex^2-1 | | 0.16(y-7)+0.18y=0.14y-0.05(10) | | 6x-4+4x+17-9x=34 | | 6w+z-5w-z= | | 3(n-4)=3 | | 15+(2+x)=(15+2)+x | | 14.5=3.4(z-12.8)-2.5 | | 3+4(2x-3)-5x=16+5 |

Equations solver categories